eDNA Detection of Native and Invasive Crayfish Species Allows for Year-Round Monitoring and Large-Scale Screening of Lotic Systems - Chucholl, Franziska; Fiolka, Franziska; Segelbacher, Gernot; Epp, Laura Saskia (Frontiers in environmental science, 2021)
Effective management of both endangered native and invasive alien crayfishes requires knowledge about distribution, monitoring of existing and early detection of newly established populations. Complementary to traditional survey methods, eDNA sampling has recently emerged as a highly sensitive non-invasive detection method to monitor crayfish populations. To advance the use of eDNA as detection tool for crayfish we used a twofold approach: 1) we designed a novel set of specific eDNA-assays for all native ( Austropotamobius torrentium, Austropotamobius pallipes, Astacus astacus ) and the most relevant invasive crayfish species ( Pacifastacus leniusculus, Faxonius limosus, Faxonius immunis ) in Central Europe. To ensure specificity each primer pair was tested in silico , in vitro, and in situ ; 2) we assessed the influence of spatio-temporal variables (distance to upstream population, season, stream size) on eDNA detection in seven streams using two different detection methods (qualitative endpoint PCR and quantitative droplet digital PCR, ddPCR). The newly developed eDNA assays successfully detected all crayfish species across different lotic and lentic habitats. eDNA detection rate (endpoint PCR) and eDNA-concentration (ddPCR) were significantly influenced by distance and season. eDNA detection was successful up to 7 km downstream of the source population and across all seasons, although detectability was lowest in winter. eDNA detection rate further decreased with increasing stream size. Finally, eDNA-concentration correlated positively with estimated upstream population size. Overall, we provide near operational eDNA assays for six crayfish species, enabling year-round detection, which represents a clear benefit over conventional methods. Due to its high sensitivity, eDNA detection is also suitable for the targeted search of as-yet unrecorded or newly emerging populations. Using quantitative ddPCR might further allow for a rough estimation of population size, provided that the identified spatio-temporal factors are accounted for. We therefore recommend implementing eDNA-detection as a complementary survey tool, particularly for a large-scale screening of data-deficient catchments or a year-round monitoring.